2018
DOI: 10.1128/aac.01348-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of the Benzoquinolizine Fluoroquinolone Levonadifloxacin (WCK 771) and Other Antimicrobial Agents against Mycoplasmas and Ureaplasmas in Humans, Including Isolates with Defined Resistance Mechanisms

Abstract: Levonadifloxacin (WCK 771) was evaluated against 68 type strains and clinical isolates of ,, , and spp. in comparison with moxifloxacin, levofloxacin, tetracycline, and azithromycin or clindamycin. Levonadifloxacin MICs were ≤0.5 μg/ml for MICs were 1 μg/ml for , 0.125 μg/ml for, and 2 μg/ml for spp. Levonadifloxacin merits further study for treating infections caused by these organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…(including macrolide-, tetracycline-, and levofloxacin-resistant strains), Chlamydophila pneumoniae, and Legionella pneumophila is established. 21,22 Anaerobes WCK 771 was found to be active against Gram-positive anaerobes such as Clostridium perfringens and C. difficile. Similarly, Gram-negative anaerobes Bacteroides fragilis, 'Prevotella and Porphyromonas strains, and β-lactamase-producing Fusobacteria were found to be susceptible to WCK 771.…”
Section: Mechanism Of Action Of Wck 771mentioning
confidence: 99%
See 1 more Smart Citation
“…(including macrolide-, tetracycline-, and levofloxacin-resistant strains), Chlamydophila pneumoniae, and Legionella pneumophila is established. 21,22 Anaerobes WCK 771 was found to be active against Gram-positive anaerobes such as Clostridium perfringens and C. difficile. Similarly, Gram-negative anaerobes Bacteroides fragilis, 'Prevotella and Porphyromonas strains, and β-lactamase-producing Fusobacteria were found to be susceptible to WCK 771.…”
Section: Mechanism Of Action Of Wck 771mentioning
confidence: 99%
“…Minimum bactericidal concentrations (MBCs) of WCK 771 were ≤2 dilutions higher than the MICs, suggesting its potential role in the treatment of infections caused by atypical bacteria with or without macrolide or tetracycline resistance. 21 Kohlhoff et al performed WCK 771 susceptibility testing against Chlamydophila pneumoniae (N=10) using HEp-2 cells grown in 96-well microtiter plates. WCK 771 MICs against these isolates ranged from 0.5 to 4 mg/L, while MIC 50/90 and MBC 90 were 1/2 mg/L and 4 mg/L, respectively.…”
Section: Mic Determination Studiesmentioning
confidence: 99%
“…When ammonia levels began to rise again, the patient was switched to a different fluoroquinolone because available susceptibility data suggest that moxifloxacin may have a lower rate of resistance. 8,9 Eventually, the patient's ammonia levels declined to normal levels by hospital day 77.…”
Section: Case Reportmentioning
confidence: 99%
“…has also been demonstrated. [7071] A recent study has demonstrated that the ratios of ELF concentration and concentration in AMs relative to plasma concentration were 7.66 and 1.58, respectively, suggesting better lung penetration. [72] Achievement of such good levels in lung combined with its broad-spectrum activity covering Gram-positive, Gram negative, and atypical pathogens, makes levonadifloxacin a potent antibiotic for the treatment of CABP.…”
Section: Future Therapiesmentioning
confidence: 99%